Treatment of resistant chronic migraine with anti-CGRP monoclonal antibodies: a systematic review - Hugo Sevivas Serralheiro (2022)
Background: Resistant chronic migraine is a highly disabling condition which is very difficult to treat. The existing prophylactic treatments for migraine are nonspecific and present weak safety profiles, leading to low adherence and discontinuation. Currently, monoclonal antibodies (mAb) targeting the trigeminal sensory neuropeptide, calcitonin gene-related peptide (CGRP), are available for migraine prophylaxis being the first drugs developed specifically to target migraine pathogenesis. The main objective of the current work is to carry out a systematic review of randomised control trials that specifically analyse the effectivity and safety of CGRP mAb, comparatively to placebo, in patients with resistant chronic migraine and possibly fill the literature gap or be a source of information to health professionals. Additionally, the current knowledge on migraine, particularly resistant chronic migraine, was revisited and summarised. Methods: Literature search was carried out on MEDLINE, Scopus, Science Direct and ClinicalTrials.gov database, from inception to December 2021. Articles were selected according to prespecified criteria of inclusion and exclusion. Efficacy and safety outcomes included were: change from baseline in monthly migraine days (MMD); ≥ 50% reduction of MMD values from baseline; change from baseline in monthly acute migraine-specific medication days (MAMD); migraine-specific quality of life questionnaire (MSQ); and registered adverse events. Additionally, we used the Cochrane risk of bias tool to assess the risk of bias of the included studies. Results: Four studies were included in this systematic review, involving 2811 resistant chronic migraine patients, 667 in a study using erenumab, 838 in a study using fremanezumab and 1306 in two studies using galcanezumab. When compared to placebo, all investigated CGRP mAb and doses demonstrate effectiveness in decreasing MMD, reducing acute medication use, and improving the MSQ scores, including, sometimes, reversion of chronic to episodic migraine (efficacy outcomes). Regarding the safety outcomes, the number and type of adverse events did not differ between CGRP mAb treated and placebo groups. Conclusions: Anti-CGRP or anti-CGRP receptor monoclonal antibodies are a promising preventive migraine therapy which can be particularly useful for resistant chronic migraine patients.